Hubungan antara Gerakan Literasi Sekolah dengan Karakter Gemar Membaca Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas III UPT SPF SD Negeri Cendrawasih Makassar - Andi Adam; Alifah Dzakilah, Nurul; Anzar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low reading interest of students at UPT SPF SD Negeri Cendrawasih Makassar, as indicated by the lack of enthusiasm toward literacy activities, the low number of library visitors, and students’ less conducive behavior during reading activities. This study aims to determine the relationship between the implementation of the School Literacy Movement (GLS) and the reading interest character in Indonesian language subjects of third-grade students at UPT SPF SD Negeri Cendrawasih Makassar. This research is a quantitative descriptive study with a correlational method. The study was conducted at UPT SPF SD Negeri Cendrawasih, Mamajang District, Makassar City. The population consisted of all third-grade students totaling 52 students, with a sample of 24 students from class III A selected using purposive sampling technique. Data collection instruments included an observation sheet to measure the implementation of the School Literacy Movement and a questionnaire in the form of multiple-choice statements to measure students’ reading interest character. The data analysis technique used descriptive statistical analysis and Pearson Product Moment correlation. The results showed that the implementation of the School Literacy Movement in the third grade at UPT SPF SD Negeri Cendrawasih was in the good category, with an average score of 31.0 out of a maximum score of 40. All students showed varying levels, ranging from less good to very good, with an equal number of 6 students in each category. Meanwhile, students’ reading interest character was also in the good category, with an average score of 61.6, where 12.5% of students were in the sufficient category, 54.2% in the good category, and 33.3% in the very good category. The results of the Product Moment correlation test showed an r-value of 0.653, which is higher than the r-table value at a 5% significance level (n-2 = 22), which is 0.433. Therefore, the research hypothesis is accepted, indicating that there is a positive and significant relationship between the implementation of the School Literacy Movement and the reading interest character of third-grade students at UPT SPF SD Negeri Cendrawasih Makassar in Indonesian language